GOVERNMENT SECURITIES MARKET IN CONDITIONS OF FINANCIAL INSTABILITY - Danyliuk , M. M.; Dmytryshyn , M. V. (The actual problems of regional economy development, 2024)
The paper deals with topical issues of the functioning of the state securities market in conditions of financial instability. The purpose of the paper is to study the theoretical and practical aspects of the functioning of the state securities market during the period of financial instability caused by a full-scale invasion. The scientific publication uses such methods of scientific research as comparison, analysis and synthesis, generalization, numerical analysis, as well as the graphic method. The economic content of state securities, their functions and purposes are studied. The advantages and disadvantages of placing state securities on the domestic and foreign markets, as well as the conditions and consequences of their issuance in national and foreign currency, are outlined. State securities are defined as a structural element of state debt and a type of economic relations between the state in the form of authorized bodies, and legal and natural persons that arise, change and terminate in the process of placing state debt securities, and the issuance of such instruments allows for the even distribution of risks and obligations communication between the issuing state and potential investors. The trends and regularities inherent in the current stage of functioning of the state securities market are highlighted, with numerical data on the current state of functioning of the debt financial instruments market in Ukraine at the current stage. The Medium-term strategy of public debt management for 2021-2024, which provides for the reduction of the share of foreign currency debt and the activation of the development of the domestic market of public debt securities, was also considered. The conducted study of conceptual approaches to the consideration of the essence of state securities allows us to define them as state debt obligations issued on behalf of state and local authorities by authorized institutions, with the aim of attracting resources to cover the budget deficit, implementing monetary regulation and financial restructuring debt obligations. Disclosure of the essence of state securities made it possible to clarify their purpose and role in the country's economy. Monitoring of the state securities market revealed its short-term nature, imperfect quantitative and qualitative composition of securities, low level of liquidity of the domestic market and a small share of institutional investors in the structure of owners of domestic state securities.